ENERGIS: Decision-Support Tool for the Implementation of Energy Policies at Urban and Regional Level. (June 2019) - Hernández Moral, G; Serna González, V I; Massa, G; Valmaseda Tranque, C
Abstract: The implementation of energy policies to reduce CO2 emissions poses specific challenges, especially to public authorities, who should define specific objectives, and evaluate the adequacy and impact of energy actions proposed. Nevertheless, an appropriate analysis is highly time-consuming due to the lack of tools. In this process, the first step is to establish the baseline energy status of the area of study. Only with this knowledge, in particular of the residential sector (main CO2 emissions contributor in cities), is it possible to plan for a low carbon economy. In this context, the ENERGIS tool will support energy planners by mapping energy demand of the residential sector at different scales, as a first step towards CO2 emissions calculation. To do so, a nationally validated Energy Performance Certification (EPC) tool has been automated, its results at building level mapped and aggregated at different scales. By basing the proposed platform on EPC calculation methodologies supported by the Energy Performance Directive of Buildings (EPBD 2010/31/EU), the ENERGIS platform achieves two main goals: it aids in the implementation of energy directives and energy actions by offering an easy to use tool to identify areas in need and, secondly, it promotes the EPBD, by making use of one of its main instruments to measure energy performance: the EPCs.